Effect of serum hepatitis B surface antigen levels on predicting the clinical outcomes of chronic hepatitis B infection: A meta‐analysis. Issue 9 (25th November 2014) - Qu, Li‐Shuai; Liu, Jin‐Xia; Zhang, Hai‐Feng; Zhu, Jing; Lu, Cui‐Hua
<x xml:space="preserve">Abstract</x> Aim The impact of serum hepatitis B surface antigen (HBsAg) levels on the prognosis of chronic hepatitis B virus (HBV) infection remains unclear. This meta‐analysis aimed to determine whether serum HBsAg levels influenced the risk of cirrhosis and hepatocellular carcinoma (HCC) development. Furthermore, we explored the role played by serum HBsAg levels in prediction of spontaneous HBsAg seroclearance. Methods We performed this meta‐analysis including 11 studies to assess the effect of HBsAg levels on predicting clinical outcomes in chronic HBV carriers. The pooled odds ratios (OR) were calculated using a random or fixed effects model. PUBMED, EMBASE, MEDLINE and the Cochrane Database were searched for articles published from 1990 to May 2014. Results Our results showed that high HBsAg levels significantly increased the risk of developing cirrhosis (OR, 2.51; 95% confidence interval [CI], 2.00–3.14; P < 0.01). Pooled data from two studies revealed that high HBsAg levels increased the risk of HCC occurrence (OR, 2.21; 95% CI, 1.52–3.22; P < 0.01). High HBsAg levels were associated with a significant increased risk of late HCC recurrence after curative resection (OR, 2.02; 95% CI, 1.48–2.77; P < 0.01), but not early recurrence (OR, 1.06; 95% CI, 0.89–1.27; P = 0.53). The pooled data indicated that low HBsAg levels were significantly in favor of spontaneous HBsAg seroclearance (OR, 7.89; 95% CI, 4.74–13.13; P < 0.01). Conclusion High HBsAg levels were associated with development of cirrhosis and HCC comparatively. Therefore, lower serum HBsAg levels were associated with a higher rate of spontaneous HBsAg seroclearance.